Features of Microbal Cenosis Forming of Alnus glutinosa (L.) Gaertn. Root Soil - Ellanskaya, Nataliia; Gorelov, Alexei (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
This article gives the results of microbiological and mycological researches of Alnus glutinosa (L.) Gaertn. root soil. The purpose of this study was to investigate the characteristics of microbial communities and their biological activity in the Alnus glutinosa plant’s root zone. The Alnus glutinosa 10 years age plants were studied in the experimental fields of the NSC Panfil Experimental Station. Microbiological investigations were carried out by conventional methods – seeding of certain dilutions of soil suspension on selective cultural medium. The allelopathic activity was analyzed by bioassays method. The comparative characteristic of microbial groups and allelopathic activity were investigated dynamically according to the Alnus glutinosa plants development phases. A quantity of actinomycetes gradual increases in spring and reduction in summer and autumn. The actinomycetes development depended on soil hydrothermal conditions. The micromycetes and ammonifiers number in the Alnus glutinosa root zone were much higher than control variation. The largest quantity of soil nitrogen consumption microorganisms was observed in summer. The soil organic matter accumulation dominated at the beginning and the end of vegetation period, whereas activation of mineralization processes occurred in summer. The number of cellulolytic microorganisms increased in the autumn, which is due to the introduction of plant residues into the soil cellulolytic activity rate correlated to cellulolytic microorganisms’ number but were significantly low. We observed the intensive growth of Azotobacter chroococcum in the root zone. It was shown that the root secretion of test plants had a small allelopathic activity. Thus, the intensity of microbiological processes depends on the season, environmental conditions and plant metabolites.